Perturbations in dopamine synthesis lead to discrete physiological effects and impact oxidative stress response in Drosophila - Hanna, Marley E. (J Insect Physiol, 2015)
The impact of mutations in four essential genes involved in dopamine (DA) synthesis and transport on longevity, motor behavior, and resistance to oxidative stress was monitored in Drosophila melanogaster. The fly lines used for this study were: (i) a loss of function mutation in Catecholamines up (Catsup(26)), which is a negative regulator of the rate limiting enzyme for DA synthesis, (ii) a mutant for the gene pale (ple(2)) that encodes for the rate limiting enzyme tyrosine hydroxylase (TH), (iii) a mutant for the gene Punch (Pu(Z22)) that encodes guanosine triphosphate cyclohydrolase, required for TH activity, and (iv) a mutant in the vesicular monoamine transporter (VMAT(Δ14)), which is required for packaging of DA as vesicles inside DA neurons. Median lifespans of ple(2), Pu(Z22) and VMAT(Δ14) mutants were significantly decreased compared to Catsup(26) and wild type controls that did not significantly differ between each other. Catsup(26) flies survived longer when exposed to hydrogen peroxide (80 μM) or paraquat (10 mM) compared to ple(2), Pu(Z22) or VMAT(Δ14) and controls. These flies also exhibited significantly higher negative geotaxis activity compared to ple(2), Pu(Z22), VMAT(Δ14) and controls. All mutant flies demonstrated rhythmic circadian locomotor activity in general, albeit Catsup(26) and VMAT(Δ14) flies had slightly weaker rhythms. Expression analysis of some key antioxidant genes revealed that glutathione S-transferase Omega-1 (GSTO1) expression was significantly up-regulated in all DA synthesis pathway mutants and especially in Catsup(26) and VMAT(Δ14) flies at both mRNA and protein levels. Taken together, we hypothesize that DA could directly influence GSTO1 transcription and thus play a significant role in the regulation of response to oxidative stress. Additionally, perturbations in DA synthesis do not appear to have a significant impact on circadian locomotor activity rhythms per se, but do have an influence on general locomotor activity levels.